C5 conserved region of hydrophilic C‐terminal part of Saccharomyces cerevisiae Nha1 antiporter determines its requirement of Erv14 COPII cargo receptor for plasma‐membrane targeting. Issue 1 (20th September 2020) - Papouskova, Klara; Moravcova, Michaela; Masrati, Gal; Ben‐Tal, Nir; Sychrova, Hana; Zimmermannova, Olga
Abstract: Erv14, a conserved cargo receptor of COPII vesicles, helps the proper trafficking of many but not all transporters to the yeast plasma membrane, for example, three out of five alkali‐metal‐cation transporters in Saccharomyces cerevisiae . Among them, the Nha1 cation/proton antiporter, which participates in cell cation and pH homeostasis, is a large membrane protein (985 aa) possessing a long hydrophilic C‐terminus (552 aa) containing six conserved regions (C1–C6) with unknown function. A short Nha1 version, lacking almost the entire C‐terminus, still binds to Erv14 but does not need it to be targeted to the plasma membrane. Comparing the localization and function of Sc Nha1 variants shortened at its C‐terminus in cells with or without Erv14 reveals that only Sc Nha1 versions possessing the complete C5 region are dependent on Erv14. In addition, our broad evolutionary conservation analysis of fungal Na + /H + antiporters identified new conserved regions in their C‐termini, and our experiments newly show C5 and other, so far unknown, regions of the C‐terminus, to be involved in the functionality and substrate specificity of Sc Nha1. Taken together, our results reveal that also relatively small hydrophilic parts of some yeast membrane proteins underlie their need to interact with the Erv14 cargo receptor. Abstract : Saccharomyces cerevisiae Erv14 is a conserved COPII cargo receptor which helps Nha1 antiporter to be properly targeted to the plasma membrane. In its long hydrophilic C‐terminus, Nha1 possesses six conserved regions (C1‐C6) with unknown function. In this work, we identified the C5 region to predetermine Nha1 requirement of Erv14, as shorter Nha1 versions lacking the C5 are Erv14 independent.